Effects of “Taking the Waist as the Axis” Therapy on trunk postural control disorder after stroke: A randomized controlled trial - Cui, Rong; Liu, Hongtao; Li, Meng; Wang, Jie; Mao, Junjie; Ni, Weidong; Wang, Furong; Pan, Jingxian; Yu, Long; Wang, Yan; Wang, Yanmin; Huang, Pufeng; et al. (Frontiers in Aging Neuroscience, 2023)
Background Sufficient attention to trunk rehabilitation after stroke is still lacking. Loss of trunk selective activity is considered to be the leading cause of trunk postural control disorder after stroke. “Taking the Waist as the Axis” Therapy (WAT) was developed as a combination of the concept of “Taking the Waist as the Axis” from Tai Chi and the rehabilitation of trunk dysfunction after stroke. The present clinical trial examined and assessed the effects of WAT on stroke patients. Methods A total of 43 stroke hemiplegic patients with trunk postural control disorder, whose Trunk Impairment Scale (TIS) scoring between 8 and 18, participated in the present study and were allocated randomly to the experimental (n = 23) or control groups (n = 20). The experimental group received WAT plus conventional therapy, and the control group received “Trunk Selective Activity” Therapy (TSAT) plus conventional therapy. Both groups received treatment once daily and 5 times per week for 3 weeks. The Trunk Impairment Scale (TIS), Fugl-Meyer Assessment (FMA), Berg Balance Scale (BBS), change of Intra-abdominal Pressure (IAP), static balance ability assessment, rapid ventilation lung function test and the Modified Barthel Index (MBI) were evaluated before and after intervention for both groups. Results The experimental group was superior to the control group in TIS [4 (2, 5) vs. 3 (1.25, 4), p = 0.030], change of IAP [−3 (−8, −1.33) vs. −0.02 (−3.08, 6), p = 0.011], FMA-upper extremity [10 (6, 18) vs. 1 (0, 3), p = 0.002], FMA-lower extremity [2 (1, 4) vs. 1 (0, 2), p = 0.009] and FMA [14 (7, 21) vs. 2 (0.25, 3.75), p = 0.001]. Within experimental group, forced vital capacity (FVC) [81.35 (63.30, 94.88) vs. 91.75 (79.40, 97.90), p = 0.02] was significantly improved. Conclusion WAT was an effective trunk treatment after stroke, which significantly improved the patients’ trunk posture control ability, motor function and forced vital capacity. However, the results still need to be interpreted with caution for the intervention only lasted for 3 weeks.